Penerapan Metode SMART (Simple Multi-Attribute Rating Technique) DalamSistemPendukungKeputusanPemberianKreditUsahaRakyat PadaBankSumut(Studi Kasus: KCPPasarMartubung) - Romindo, Romindo; Hardianti, Siti (Journal of Computer Networks, Architecture and High Performance Computing, 2019)
Bank SUMUT KCP Pasar Martubung in the provision of People's Business Credit (KUR) and the subject of this research is the People's Business Credit Account (KUR), which amounts to one person. The high interest of the community in obtaining KUR made it difficult for Bank SUMUT to determine who was entitled to receive KUR. In the process of determining the eligibility of previous KUR recipients, the method of comparison between monthly income and monthly needs is still using the manual method. This method is considered to be still simple, this is due to dependence on one indicator that causes bad credit. To overcome this problem, a decision support system is needed with the SMART Multi Attribute Ranking Technique which can assist in the provision of KUR to the community that meets the criteria in the provision of KUR